Effect of Neoadjuvant Chemoradiotherapy with Capecitabine versus Fluorouracil for Locally Advanced Rectal Cancer: A Meta-Analysis - Guo-Chen Liu; Jun-Ping Yan; Qing He; Xin An; Zhi-Zhong Pan; Pei-Rong Ding (Gastroenterology Research and Practice)
A meta-analysis was carried out to compare the efficacy and safety of capecitabine plus radiation with 5-fluorouracil (5-FU) plus radiotherapy (RT) as neoadjuvant treatment in locally advanced rectal cancer (LARC). We searched the Cochrane database, Ovid, Medline, Embase, ISI databases, and Chinese Biomedical Literature Database between January 1998 and October 2014. Trials of capecitabine compared with 5-FU plus RT as neoadjuvant treatment for LARC were considered for inclusion. RevMan software was used to analyze these data. Nine trials were included in this meta-analysis, which covered a total of 3141 patients. The meta-analysis showed that capecitabine group had statistically significant better pCR rates (OR, 1.34; 95% CI, 1.10–1.64; P=0.003), T downstaging rates (OR, 1.58; 95% CI, 1.22–2.06; P=0.0007), N downstaging rates (OR, 2.06; 95% CI, 1.34–3.16; P=0.001), less distant metastasis (OR, 0.63; 95% CI, 0.44–0.88; P=0.007), and lowered leucocytes (OR, 0.25; 95% CI, 0.11–0.54; P=0.0005), but with higher incidence of hand-foot syndrome (HFS) (OR, 4.43; 95% CI, 1.59–12.33; P=0.004). Capecitabine was more efficient than 5-FU in terms of tumor response in neoadjuvant treatment for patients with LARC and favourably low toxicity with the exception of HFS.